2022
DOI: 10.1038/s41597-022-01615-9
|View full text |Cite
|
Sign up to set email alerts
|

ASL-BIDS, the brain imaging data structure extension for arterial spin labeling

Abstract: Arterial spin labeling (ASL) is a non-invasive MRI technique that allows for quantitative measurement of cerebral perfusion. Incomplete or inaccurate reporting of acquisition parameters complicates quantification, analysis, and sharing of ASL data, particularly for studies across multiple sites, platforms, and ASL methods. There is a strong need for standardization of ASL data storage, including acquisition metadata. Recently, ASL-BIDS, the BIDS extension for ASL, was developed and released in BIDS 1.5.0. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…The results in Table 2 showed that the volume and CBF values of brain regions such as frontal lobe, temporal lobe, and basal ganglia were lower in ADHD children than in healthy children, suggesting poor development of those brain regions and decreased CBF perfusion in ADHD children. The poor development of frontal lobe, temporal lobe, and basal ganglia in ADHD children may be due to the poor development of brain regions caused by longterm inadequate blood perfusion in these three brain regions, which ultimately leads to the development of clinical symptoms such as hyperactivity in ADHD children (42)(43)(44). The results showed that the gray matter volume and CBF values of brain regions such as frontal lobe, temporal lobe and basal ganglia were lower in ADHD children with ADHD than in healthy children, but only the volume of white matter was lower than in healthy children, and the difference in CBF values was not statistically significant, suggesting that the microstructural changes in the brain of ADHD children are mainly in the gray matter, which is probably because there is more blood flow in the gray matter and less blood flow in the white matter.…”
Section: Discussionmentioning
confidence: 99%
“…The results in Table 2 showed that the volume and CBF values of brain regions such as frontal lobe, temporal lobe, and basal ganglia were lower in ADHD children than in healthy children, suggesting poor development of those brain regions and decreased CBF perfusion in ADHD children. The poor development of frontal lobe, temporal lobe, and basal ganglia in ADHD children may be due to the poor development of brain regions caused by longterm inadequate blood perfusion in these three brain regions, which ultimately leads to the development of clinical symptoms such as hyperactivity in ADHD children (42)(43)(44). The results showed that the gray matter volume and CBF values of brain regions such as frontal lobe, temporal lobe and basal ganglia were lower in ADHD children with ADHD than in healthy children, but only the volume of white matter was lower than in healthy children, and the difference in CBF values was not statistically significant, suggesting that the microstructural changes in the brain of ADHD children are mainly in the gray matter, which is probably because there is more blood flow in the gray matter and less blood flow in the white matter.…”
Section: Discussionmentioning
confidence: 99%
“…Less than half of the pipelines support imports from the clinically used DICOM format (n = 9). Only three pipelines support ASL‐BIDS, 32 the recently developed ASL extension of the standard for storing image data and acquisition metadata. All pipelines were developed for human brain data, and only a few were reported to be suited also for body imaging in humans (n = 3) and preclinical brain imaging (n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…20 More than 20 different toolboxes have been released for ASL data processing and analysis 16,19,[21][22][23][24][25][26][27][28][29][30][31] from different laboratories that specialize in ASL analysis. The selection of a particular pipeline by a new user can be complicated because of the wide variety of ASL sequences, data formats, 32 and processing methods. 19 Both new and experienced ASL users looking for suitable ASL image processing and quantification software may benefit from a comprehensive and detailed list of ASL image-processing software along with their features to guide their search for a suitable pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters related to ASL labeling methods are provided in Table 5. In general, the names and definitions of parameters comply with the ASL White Paper, 1 as well as ASL-BIDS 4 ; otherwise, the difference is provided in the description. In general, for timing parameters there is no preference between the use of "ms" and "s." In ASL-BIDS, however, the values in JSON sidecars are entered without specifying the units; therefore, the use of correct units, as specified in the ASL-BIDS definition, should be strictly followed.…”
Section: Parameters In Asl Labeling Methodsmentioning
confidence: 99%